2010
DOI: 10.1080/15533174.2010.522662
|View full text |Cite
|
Sign up to set email alerts
|

Friendly Synthesis, Metallation, and Phosphorylation of Schiff Base as a Potential Pharmacological Interest

Abstract: In view of the broad physiological activity of organometallic and organophosphorus compounds, the present paper deals with the synthesis of 2-(4-methoxybenzylidene amino) benzene-thiol, its metallation with mercury (II), nickel (II), palladium (II), and phosphorylation. The antimicrobial activities of all products were investigated. The palladated product displays a significant anticancer activity against human breast carcinoma cell. All the new products were investigated and their structures were elucidated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[1] New Schiff bases synthesized by More et al [2] from substituted 2-aminothiazole and substituted salicylaldehydes or 2-hydroxy-1-naphthaldehyde were found to exhibit antibacterial and antifungal activities. El-Sawi et al [3] described the reaction of isatin with 1,3-propanediamine giving rise to two pairs of isomeric new Schiff bases, where each of isomers differs from the other according to the mode of addition. El-Sawi et al [4] reported that metallation of some dyes such as direct orange-26 gave new metallated compounds via substitution reaction, C-N bond cleavage, and desulfonation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[1] New Schiff bases synthesized by More et al [2] from substituted 2-aminothiazole and substituted salicylaldehydes or 2-hydroxy-1-naphthaldehyde were found to exhibit antibacterial and antifungal activities. El-Sawi et al [3] described the reaction of isatin with 1,3-propanediamine giving rise to two pairs of isomeric new Schiff bases, where each of isomers differs from the other according to the mode of addition. El-Sawi et al [4] reported that metallation of some dyes such as direct orange-26 gave new metallated compounds via substitution reaction, C-N bond cleavage, and desulfonation reaction.…”
Section: Introductionmentioning
confidence: 99%